Webinar Nasional Meningkatkan Daya Saing UMKM di Era Digital Tentang Inovasi Pertumbuhan Ekonomi Melalui E-commerce - M Arief Rahman; Kusmayanti; Hary Jocom (Universitas Merdeka Surabaya, 2024)
MSMEs in Indonesia face significant challenges in improving competitiveness in the digital era. To address this issue, a national webinar was held with the aim of discussing economic growth innovation through e-commerce. The implementation of this webinar used a qualitative approach method, starting with the identification of MSME needs and continued with training covering digital marketing strategies and online store management. The webinar involved participants from various regions who were active in discussion sessions and hands-on practice. Evaluation showed that participants experienced an increase in knowledge and skills in e-commerce, allowing them to compete more effectively in the global market.